2016
DOI: 10.1159/000448027
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Physical Activity Associated with Executive Dysfunction Correlates with Cognitive Impairment among Older Adults in the Community: A Retrospective Analysis from the Kurihara Project

Abstract: Background/Aims: No previous studies have explored the relationship between physical activity (PA) and executive dysfunction. Methods: We retrospectively evaluated the PA for 590 older participants in the Kurihara Project; 221 participants had a Clinical Dementia Rating (CDR) of 0 (healthy), 295 CDR 0.5 (very mild dementia), and 74 CDR 1+ (dementia). Results: In the complicated task, whether the motor intensity was high (e.g. farming) or low (e.g. shopping), PA exhibited an inverse relationship with the CDR le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…One systematic review found a mean daily step count of 2,237 [129], which is far less than the threshold for a low active (5,000 steps) or active lifestyle (10,000 steps) indicated by the same authors [129]. Low physical activity levels and a sedentary lifestyle negatively impact on cognition in the general population [130,131], and as such may contribute to CI in COPD as well.…”
Section: Inactive Lifestylementioning
confidence: 96%
“…One systematic review found a mean daily step count of 2,237 [129], which is far less than the threshold for a low active (5,000 steps) or active lifestyle (10,000 steps) indicated by the same authors [129]. Low physical activity levels and a sedentary lifestyle negatively impact on cognition in the general population [130,131], and as such may contribute to CI in COPD as well.…”
Section: Inactive Lifestylementioning
confidence: 96%
“…Understanding the correlates of PA in MCI is important for multiple health reasons, including the enhancement of executive function 21 for the maintenance of personal autonomy 22 and reducing caregiver burden 23 . In addition to the overall lack of information on factors influencing PA participation in people with MCI, very little is known about PA correlates in older people in LMICs in general.…”
Section: Introductionmentioning
confidence: 99%
“…After retirement, most elderly people would be concerned with activities related to their home and hobbies. However, elderly people with very mild dementia exhibited disabilities of complicated IADL activities in the home, such as shopping and food preparation ( Kobayashi et al, 2016 ; Ouchi et al, 2016 ). Cognitive impairments, especially executive dysfunction, quantitatively and qualitatively decreased the complicated IADL activities in patients with very mild dementia ( Ouchi et al, 2016 ) in spite of the intensity of physical activity ( Kobayashi et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, elderly people with very mild dementia exhibited disabilities of complicated IADL activities in the home, such as shopping and food preparation ( Kobayashi et al, 2016 ; Ouchi et al, 2016 ). Cognitive impairments, especially executive dysfunction, quantitatively and qualitatively decreased the complicated IADL activities in patients with very mild dementia ( Ouchi et al, 2016 ) in spite of the intensity of physical activity ( Kobayashi et al, 2016 ). We need specific rehabilitation of and care for dysfunctions of activities related to home and hobbies among elderly people with very mild dementia through physical, psychological, social, and environmental supports.…”
Section: Discussionmentioning
confidence: 99%